A conformally bonded molecular interface retarded iodine migration for durable perovskite solar cells. Issue 4 (1st March 2023) - Yuan, Ligang; Zhu, Weiya; Zhang, Yiheng; Li, Yuan; Chan, Christopher C. S.; Qin, Minchao; Qiu, Jianhang; Zhang, Kaicheng; Huang, Jiaxing; Wang, Jiarong; Luo, Huiming; Zhang, Zheng; et al.
Abstract : A molecular hole transport material retards the iodine migration and delivers high stability in a harsh 85 °C MPP test. Abstract : State-of-the-art n–i–p perovskite solar cells (PSCs) suffer from stability issues due to ionic interdiffusion. Herein, by enlarging the indacenodithiophene π-bridge donor (D′) to combine with the methoxy triphenylamine donor (D) and benzothiadiazole acceptor (A), three linear molecules termed L1, L2 and L3 with a D–A–D′–A–D structure are developed as dopant-free hole transport materials (HTMs). The π-bridge extension with active sites for coordination leverages the intramolecular dipole effect and intermolecular packing effect, resulting in a conformally bonded ultrathin interface with compact and uniform coverage (∼60 nm) to retard iodine migration and protect the buried perovskite. The unencapsulated L3-PSC (ITO/SnO2 /perovskite/L3/MoO3 /Au) achieved an impressive PCE of 22.61% (certified 21.79%, 0.0525 cm 2 ). Ultrafast laser spectroscopy reveals that L-series molecules have a sequential reduction of photoexcited energy disorder to illustrate the structure–performance–stability relationship. L3-PSC maintains over 85% of the initial efficiency after 500 h at 85 °C maximum power point tracking (MPP) and enables the possibility of using small molecules to stabilize n–i–p PSCs.